(untitled) (Analysis in Theory and Applications, 2022)
A significant number of studies have been carried out on the generalized Lebesgue spaces L^p(x), Sobolev spaces W^1,p(x) and Herz spaces. In this paper, we demonstrated a characterization of boundedness of the fractional maximal operator with variable kernel on Herz-Morrey spaces.